The context of special pedagogy: practical inclusive education or simulated inclusive education? - Barłóg, Krystyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Krystyna Barłóg, The centex of special pedagogy: implementedinclusive education or simulated inclusive education? Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 125–142. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.06 In many contexts of contemporary special education, its main present and future challenges are the implementation of effective inclusive education, the preparation of the required conditions, space and relations of safe functioning of a child with disabilities or special education needs together with healthy, able-bodied peers. Are the long-standing dreams of parents and many special educators regarding the equal rights of all people with disabilities, and in particular the right to education closest to the child’s place of residence, genuinely achieved nowadays? The diagnosis of selected municipal schools shows the real situation of the implementation of inclusive education. Are these successes already being achieved today? Or is it still a educational reality?